Intradermally Administered Retinoic Acid or Vitamin D3-Loaded Liposomes Induce Tolerogenic Skin Dendritic Cells - Noémi Anna Nagy; Sanne G. Celant; Toni M. M. van Capel; Rinske Sparrius; Fernando Lozano Vigario; Ronald van Ree; Bram Slütter; Teunis B. H. Geijtenbeek; Sander W. Tas; Esther C. de Jong (Journal of Immunology Research)
In vivo targeting of dendritic cells (DCs) with nanocarriers containing tolerogenic adjuvants is an attractive strategy to dampen inflammation. Here, we used ex vivo skin vaccination to examine the effect of intradermal injection of liposomes loaded with the tolerogenic adjuvants all-trans retinoic acid (RA) and vitamin D3 (VD3). We investigated the effect of intradermal liposome injection on skin DCs and the skin DC-induced T cell response. Our study shows that intradermal injection of RA or VD3-loaded anionic phospholipid 1,2-distearoyl-sn-glycero-3-phosphoglycerol (DSPG) liposomes selectively induces CD14+ dermal DC (DDC) migration while reducing migration of CD1a dim DDCs. Migrated CD14+ DDCs displayed a partially immature phenotype. RA or VD3 liposome-treated CD1a dim DDCs exhibited reduced expression of maturation markers and induced expression of coinhibitory immunoglobulin-like transcript 3 (ILT3). VD3 liposome-treated CD14+ DDCs, as well as, CD1a dim DDCs, exhibited reduced expression of maturation markers, induction of coinhibitory molecules ILT3, and programmed death-ligand 1 (PD-L1). Migrated DCs from RA or VD3 liposome-injected skin differentiated naïve CD4+ T cells into FoxP3+ CD127 low and ICOS+ Tregs, expressing functional regulatory markers. Thus, our findings provide further substantiation for in vivo DC-modulating vaccines with tolerogenic liposomes as a putative clinical therapy for autoimmune diseases and allergies.